Effect of a freeze-dried coffee solution in a high-fat diet-induced obesity model in rats : impact on inflammatory response, lipid profile, and gut microbiota - Cavalcanti, Marilia Hermes (2022)
Coffee beans contain high polyphenol content, which have the potential to modulate the intestinal microbiota, and possibly attenuate weight gain and the associated dyslipidemia. This study investigated the effect of freeze-dried coffee solution (FCS) consumption on physiological parameters, lipid profile, and microbiota of Wistar rats fed a high-fat diet (HF) or control diet (CT). FCS combined with a high-fat diet increased the fecal and cecal Bifidobacterium spp. population and decreased the cecal Escherichia coli population and intestinal Il1b mRNA level. Regardless of the diet type, FCS increased the serum high-density lipoprotein cholesterol (HDL-C); however, it did not affect body weight, food intake, low-density lipoprotein, triglycerides, fecal bile acids, and intestinal Il6 mRNA levels. The high-fat diet increased weight gain, hepatic cholesterol and triglycerides, fecal bile acids, and the fecal and cecal Lactobacillus spp. population, and reduced food intake, the fecal E. coli population, and intestinal Il6 mRNA level. The results suggest that FCS consumption exhibits positive health effects in rats fed a high-fat diet by increasing Bifidobacterium spp. population and HDL-C reverse cholesterol transport, and by reducing Il1b mRNA level. However, FCS administration at a dose of 0.39 g/100 g diet over an eight-week period was not effective in controlling food intake, and consequently, preventing weight gain in rats of high-fat diet-induced obesity model.